Rethinking Te Aro in the 1910s - Jacob, James (Architectural History Aotearoa, 2022)
Wellington’s Te Aro neighbourhood is particularly notable for both its broad expanse of relatively flat land and for its rectilinear grid of streets and associated superblocks in a city otherwise known for its hills and irregular road system. Over the course of the nineteenth-century after the start of European settlement in 1840, the town acres within the superblocks of Te Aro were more intensively developed in myriad ways, resulting in a haphazard arrangement of worker dwellings, commercial premises, and industrial outfits aligned along largely private lanes and alleys. With the notable exception of the street grid, nearly all vestiges of this initial, Victorian-era development were progressively destroyed during the twentieth century. Although most of the architectural and urban reinvention of Te Aro did not occur until the decades following World War II, acknowledgment of the major factors that would ultimately contribute to this process - traffic congestion, the low quality of the existing building stock, and a strong shift away from residential functions - became more and more emphasised during the 1910s. A writer for the Evening Post in 1913 imagined the neighbourhood just seven years in the future: "the dingy wooden boxes on Te Aro Flat will have given place to handsome warehouses and shops and factories …The problem of traffic, already threatening trouble … is certainly a task for the ablest engineer nowadays to suggest a way out" (Autos "The Future" p 3). This degree of optimism for rapid change was quickly tempered by the realities of world war and, in retrospect, the 1910s can be interpreted as a period of incubation for ideas about architecture urban planning in Te Aro that would only come to fruition later in the century.